Medicaid Patients Have Greater Difficulty Scheduling Health Care Appointments Compared With Private Insurance Patients: A Meta-Analysis. (April 2019) - Hsiang, Walter R.; Lukasiewicz, Adam; Gentry, Mark; Kim, Chang-Yeon; Leslie, Michael P.; Pelker, Richard; Forman, Howard P.; Wiznia, Daniel H.
Medicaid patients are known to have reduced access to care compared with privately insured patients; however, quantifying this disparity with large controlled studies remains a challenge. This meta-analysis evaluates the disparity in health services accessibility of appointments between Medicaid and privately insured patients through audit studies of health care appointments and schedules. Audit studies evaluating different types of outpatient physician practices were selected. Studies were categorized based on the characteristics of the simulated patient scenario. The relative risk of appointment availability was calculated for all different types of audit scenario characteristics. As a secondary analysis, appointment availability was compared pre- versus post-Medicaid expansion. Overall, 34 audit studies were identified, which demonstrated that Medicaid insurance is associated with a 1.6-fold lower likelihood in successfully scheduling a primary care appointment and a 3.3-fold lower likelihood in successfully scheduling a specialty appointment when compared with private insurance. In this first meta-analysis comparing appointment availability between Medicaid and privately insured patients, we demonstrate Medicaid patients have greater difficulty obtaining appointments compared with privately insured patients across a variety of medical scenarios.